Prosthetic Complications of Single Screw-Retained Implant-Supported Metal–Ceramic Fixed Prostheses: A Retrospective Observational Study - Cristina Palma-Carrió; Andrea Macconi; Andrea Rubert-Aparici; Paula Vidal-Peiró; Isabel Menéndez-Nieto; Juan Antonio Blaya-Tárraga (International Journal of Dentistry)
Purpose. To analyze prosthetic complications of single screw-retained implant-supported metal–ceramic fixed prostheses (SSIMCFPs). Materials and Methods. A total of 457 medical records of patients treated with implants at the University Dental Clinic of the European University of Valencia from 2016 to 2022 were reviewed. Of the 335 SSIMCFPs evaluated, 222 were included. The following data were collected from medical records: age, sex, prosthesis location, implant diameter, type of antagonist, date of prosthesis placement, type of prosthetic complications, and the date of the occurrence of complications. Statistical analysis was estimated at the patient level with a simple binary logistic regression and at the prosthesis level, a simple logistic regression with generalized estimating equation models (p <0.05). Results. A total of 222 SSIMCFPs were placed in 159 patients. The prevalence of complications was 23.3% at the patient level, equivalent to 21.6% of SSIMCFPs. A total of 48 complications were collected; screw loosening was the most frequent complication (16.2%), followed by ceramic fracture (3.1%), screw fracture (1.8%), and implant fracture (0.5%). There were no cases of abutment fracture. The mean time of the loosening of the screw was 10.5 months and ceramic fractures at 6.9 months. The factors that most influenced the occurrence of prosthetic complications were posterior position (p <0.001), implant diameter from 3.5 to 4.8 mm (p <0.01), and lower arch position (p <0.05). Conclusions. The most frequent complication of SSIMCFP was loosening of the screw followed by ceramic fracture. The appearance of these complications usually occurred during the first year after SSIMCFP placement. Factors related to the occurrence of complications were mandibular posterior location and implant diameter from 3.5 to 4.8 mm.